2021
DOI: 10.1016/j.redox.2021.102174
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis-dependent extracellular vesicles from macrophage contribute to asbestos-induced mesothelial carcinogenesis through loading ferritin

Abstract: Asbestos-associated diseases remain a social burden worldwide. Our previous studies identified asbestos-induced iron-rich milieu for mesothelial cells with ceaseless macrophage ferroptosis. However, molecular mechanisms how this mutagenic milieu influences mesothelial cells have not been elucidated yet. Here, we propose a novel mechanism that extracellular vesicles (EVs) mediate asbestos-associated mutagenic factors to mesothelial cells. In a mice model of intraperitoneal crocidolite injection, mutagenic milie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 42 publications
2
58
0
Order By: Relevance
“… Dai et al (2020) demonstrated for the first time a link between ferroptotic cells and macrophages, that is, exosomes released by ferroptotic pancreatic cancer cells carry KRAS protein to macrophages, resulting in the M2 polarization of macrophages. Ito et al (2021) first evidenced that ferroptosis-dependent EVs from macrophage by loading ferritin contribute to mesothelial carcinogenesis ( Ito et al, 2021 ). These results led us to wonder whether ferroptotic cardiomyocytes acted on macrophages function change through exosomes.…”
Section: Discussionmentioning
confidence: 99%
“… Dai et al (2020) demonstrated for the first time a link between ferroptotic cells and macrophages, that is, exosomes released by ferroptotic pancreatic cancer cells carry KRAS protein to macrophages, resulting in the M2 polarization of macrophages. Ito et al (2021) first evidenced that ferroptosis-dependent EVs from macrophage by loading ferritin contribute to mesothelial carcinogenesis ( Ito et al, 2021 ). These results led us to wonder whether ferroptotic cardiomyocytes acted on macrophages function change through exosomes.…”
Section: Discussionmentioning
confidence: 99%
“…FedEVs contain a high amount of iron-loaded ferritin and of note are taken up by the mesothelial cells present at the surface of somatic cavities, eventually causing oxidative DNA damage. (110) Thus, iron sharing system may lead to harmful effects under the situation of monopoly, where the individual tries not to release any subtle amount of iron to the other infected species or their equivalents. (111)…”
Section: Iron and Extracellular Vesiclesmentioning
confidence: 99%
“…Ferritin is composed of ferritin heavy polypeptide 1 (FTH1) and ferritin light polypeptide 1, and functions as the major iron sequestration and storage protein to decrease intracellular iron concentrations. In contrast, ferritin proteolytic degradation leads to rapid releases of iron, and subsequently increases intracellular iron levels and ferroptosis [ [13] , [14] , [15] ]. Nuclear receptor coactivator 4 (NCOA4) is identified as a cargo receptor for the autophagic degradation of ferritin that is known as ferritinophagy, and NCOA4-mediated ferritin turnover contributes to the elevation of intracellular iron levels and subsequent ferroptosis in different cell types, including the glioblastoma cells [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%